Countering the discriminatory impact of minimum wages against disadvantaged workers: Literature review and experimental design development - Aniceto C. Orbeta; Vicente B. Paqueo (Philippine Institute for Development Studies (PIDS), 2017)
It is a common belief that government should set legal minimum wages (LMW) to a level that would enable workers and their families to live decent lives. Evidence, however, has shown that a higher and more rapid pace of LMW growth leads to lower demand for labor overall. Specifically, it leads to reduced hours, lower employment rate, reduced household income, and higher poverty incidence. In addition, these adverse effects impact particularly disadvantaged population groups that include the young, inexperienced, low educated, and women - in general, people with little human capital and poor job credentials. On this score, it is arguable that the government is morally obligated to attenuate the above discriminatory effects against the poor and disadvantaged - effects that were created by its labor regulations. The question is: How? More precisely, what are affordable interventions to effectively address the issue? This research reviews the global experience on initiatives to counter the discriminatory impact of LMW and related labor regulations. It also summarizes the analyses done to date for similar programs in the country. Knowledge gained from the review would be used to design an experimental study measuring impact of such initiatives. Some design ideas on evaluating these programs are also presented.
Keywords: 330; Active labor market programs; minimum wage; impact evaluation; Philippines